EphA4 is Involved in Sleep Regulation but Not in the Electrophysiological Response to Sleep Deprivation. Issue 3 (1st March 2016) - Freyburger, Marlène; Pierre, Audrey; Paquette, Gabrielle; Bélanger-Nelson, Erika; Bedont, Joseph; Gaudreault, Pierre-Olivier; Drolet, Guy; Laforest, Sylvie; Blackshaw, Seth; Cermakian, Nicolas; Doucet, Guy; Mongrain, Valérie
Abstract: Study Objectives: Optimal sleep is ensured by the interaction of circadian and homeostatic processes. Although synaptic plasticity seems to contribute to both processes, the specific players involved are not well understood. The EphA4 tyrosine kinase receptor is a cell adhesion protein regulating synaptic plasticity. We investigated the role of EphA4 in sleep regulation using electrocorticography in mice lacking EphA4 and gene expression measurements. Methods: EphA4 knockout (KO) mice, Clock Δ 19 /Δ 19 mutant mice and littermates, C57BL/6J and CD-1 mice, and Sprague-Dawley rats were studied under a 12 h light: 12 h dark cycle, under undisturbed conditions or 6 h sleep deprivation (SLD), and submitted to a 48 h electrophysiological recording and/or brain sampling at different time of day. Results: EphA4 KO mice showed less rapid eye movement sleep (REMS), enhanced duration of individual bouts of wakefulness and nonrapid eye movement sleep (NREMS) during the light period, and a blunted daily rhythm of NREMS sigma activity. The NREMS delta activity response to SLD was unchanged in EphA4 KO mice. However, SLD increased EphA4 expression in the thalamic/hypothalamic region in C57BL/6J mice. We further show the presence of E-boxes in the promoter region of EphA4, a lower expression of EphA4 in Clock mutant mice, a rhythmic expression of EphA4 ligands in several brain areas, expression of EphA4 in the suprachiasmatic nuclei of the hypothalamus (SCN), and finally an unchanged number of cells expressing Vip, Grp and Avp in the SCN of EphA4 KO mice. Conclusions: Our results suggest that EphA4 is involved in circadian sleep regulation. Significance: Our study provides the first findings supporting a role for the ephrin and Eph receptor cellular adhesion system in the regulation of sleep duration, sleep consolidation and synchronous activity of the cerebral cortex. It presents novel insight into molecular mechanisms involved in sleep regulation and more specifically on how molecules involved in synaptic plasticity participate in the control of wakefulness and sleep states. Given that the ephrin/Eph system has been linked to both neuronal development and neurodegeneration, our results highlight a new pathway, not only linking sleep to synaptic plasticity, but also connecting sleep alterations to neurodevelopmental and neurodegenerative diseases.